Modification of Land Conservation on Agriculture Based on Environmental Mitigation in Biosequent Marapi - Dedi Hermon (Pascasarjana, Universitas Negeri Padang, 2020)
Intention of this research is to study distribution of erodibilitas for the instruction of conservation agriculture which have base development of have continuation to pursuant to biosequent in Marapi West Sumatra and give solution about ideal and compatible conservation technique type used by farmer society to increase and maintain erodibilitas in managing farm for the agriculture. Method the used i] method of survey with technique intake of sampel by stratified random sampling. Result of research obtained by ideal conservation at permanent plant cover, sequentalcropping+mulsa, and bench terrace+mulsa+waterway. While conservation which is not ideal to be applied is contur strip cropping, maximum tillage+intercropping, and bench terrace. Other pertained at conservation rather ideal.